Functional characterization of MdMYB73 reveals its involvement in cold stress response in apple calli and Arabidopsis - Quan-yan ZHANG; Jian-qiang YU; Jia-hui WANG; Da-gang HU; Yu-jin HAO (Journal of Integrative Agriculture, 2017)
Abstract: Recent studies have shown that the R2R3-MYB transcription factor MdMYB73 is involved in salt stress response in apple. However, no research was done whether MdMYB73 mediated cold tolerance in apple or not. In this study, we found that the expression of MdMYB73 was obviously induced by cold stress. Functional analysis showed that MdMYB73 significantly increased cold tolerance in transgenic apple calli and Arabidopsis. Quantitative real-time PCR (qRT-PCR) assay indicated that the expression levels of cold-responsive genes including MdCBF2, MdCBF3, MdCBF4, and MdCBF5 were obviously enhanced in MdMYB73 transgenic calli, suggesting that MdMYB73 increased cold tolerance via C-repeat binding factor (CBF) cold response pathway. Finally, we found that soluble sugar, which provides an osmoticum for cells, was increased in MdMYB73 transgenic calli compared to that in the wild type control. These findings provide a new insights into how MdMYB73 is involved in cold stress response.